1992
DOI: 10.1093/hsw/17.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers' Knowledge about AIDS: Working with Vulnerable and Oppressed People

Abstract: This study assessed social workers' differential knowledge about human immunodeficiency virus (HIV) infection. A questionnaire was mailed to a random sample of 500 members of the National Association of Social Workers in July 1988. Results show that social workers have the most information regarding transmission of HIV infection and the least information about the effects of HIV on specific subpopulations. Of particular concern was that respondents who stated they had either a personal or professional reason f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In their study on the attitudes and knowledge of alumni from the Kentucky School of Social Work, Dhooper, Royse and Tran (1987-88) found that 67% of their sample were moderately or highly fearful of AIDS and that there was little evidence of the participants being well-informed about AIDS. In a nationwide study using a random sample of 379 social workers to assess their knowledge level, Peterson (1991) found that the percentage of incorrect answers was much lower than the percentage of 'don't know' responses. She concluded that respondents were more likely to be uninformed than to be misinformed.…”
mentioning
confidence: 99%
“…In their study on the attitudes and knowledge of alumni from the Kentucky School of Social Work, Dhooper, Royse and Tran (1987-88) found that 67% of their sample were moderately or highly fearful of AIDS and that there was little evidence of the participants being well-informed about AIDS. In a nationwide study using a random sample of 379 social workers to assess their knowledge level, Peterson (1991) found that the percentage of incorrect answers was much lower than the percentage of 'don't know' responses. She concluded that respondents were more likely to be uninformed than to be misinformed.…”
mentioning
confidence: 99%
“…These findings are especially significant given that the sample consists primarily of social workers and nurses, the two professions which are most seriously committed to assisting people in need. As Peterson (1991) acknowledges, professionals are not immune to the fear and misinformation found in the general public. Indeed, there is an extensive literature concerning professionals' attitudes to AIDS and their relationship to stereotypes regarding homosexuals and drug users who are commonly associated with the spread of the disease (Bachelor, 1988;Silberman, 1991;Young, 1988;Blumenfield et al, 1987;Dhooper et al, 1987-8;Dworkin et al, 1991: Gillman, 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Dhooper et al (1987-8) evaluated the attitudes and knowledge of alumni from the Kentucky School of Social Work and found that 67 percent of their sample were moderately or highly fearful of AIDS and that there was little evidence of participants in their sample being well informed about AIDS. In a nationwide study using a random sample of 379 social workers to assess their knowledge level, Peterson (1991) found that the percentage of incorrect answers was much lower than the percentage of 'don't know'…”
mentioning
confidence: 99%
“…Overwhelmingly, findings indicate a significant correlation between knowledge and positive attitudes toward persons with AIDS (Ben-Ari, 1996; Dhooper et al, 1987-88;Furstenberg & Olson, 1984;Gillman, 1991;Harrison et al, 1990;Knight, 1996;Merdinger et al, 1990;Owens, 1995;Peterson, 1991;Riley & Greene, 1993;Royse et al, 1987;Sachdev, 1998;Shi et al, 1993;Soliman & Mizanur, 1998;Strouse, 1990;Wexler, 1989;Wiener-Brawerman, 1988;Wiener & Siegel, 1990). Similar results have also been found within medicine (Bernstein et al, 1990;Feldman et al, 1990); nursing (Bowman et al, 1994;Scherer et al, 1991;West et al, 1996); mental health counseling (Castro et al, 1993;Dow & Knox, 1991;Turner, 1992); as well as with college students in general (Brandyberry & McNair, 1996;Connors & Heaven, 1995;Fennell, 1990;Goh, 1993;James & Frese, 1993;Ploem & Byers, 1997;Scollay et al, 1992;Strauss et al, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%